2016
DOI: 10.1585/pfr.11.2406025
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Acetic Acid in Water Using Gas-Liquid Plasma with SPG Membrane

Abstract: The gas-liquid mixed phase plasma generated by a nanoseconds-pulsed discharge in bubbles was used for degradation of acetic acid in water. A Shirasu porous glass (SPG) membrane tube was adopted as micro-bubble generator and part of a discharge reactor. A large number of tiny bubbles are generated from dense micro-pores (average diameter of φ50 µm) of the SPG wall and a discharge through SPG membrane was initiated between high voltage electrode and bubble surface. Comparing with a resin tube reactor which has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…One type of AOPs is plasma generation in contact with water, which has been studied in water treatment for several decades [3][4][5][6]. Many types of plasma treatment have been proposed, including pulsed corona discharge in water [7], direct current (DC) or pulsed corona discharge over water [8][9][10], pulsed discharge over water without/with gas bubbling [11][12][13], DC or pulsed discharge in bubbles [14][15][16][17], dielectric-barrier discharge (DBD) in a gas-liquid two-phase flow [18,19], microwave plasma in water [20], and DBD in a mist flow [21]. A wide range of processing speeds and energy efficiencies have been observed for the reduction of total organic carbon (TOC), and it was revealed that hydrogen peroxide (H 2 O 2 ) generated by a self-quenching reaction of OH radicals acts as OH radical scavengers, which limits the processing speed and energy efficiency [11].…”
Section: Introductionmentioning
confidence: 99%
“…One type of AOPs is plasma generation in contact with water, which has been studied in water treatment for several decades [3][4][5][6]. Many types of plasma treatment have been proposed, including pulsed corona discharge in water [7], direct current (DC) or pulsed corona discharge over water [8][9][10], pulsed discharge over water without/with gas bubbling [11][12][13], DC or pulsed discharge in bubbles [14][15][16][17], dielectric-barrier discharge (DBD) in a gas-liquid two-phase flow [18,19], microwave plasma in water [20], and DBD in a mist flow [21]. A wide range of processing speeds and energy efficiencies have been observed for the reduction of total organic carbon (TOC), and it was revealed that hydrogen peroxide (H 2 O 2 ) generated by a self-quenching reaction of OH radicals acts as OH radical scavengers, which limits the processing speed and energy efficiency [11].…”
Section: Introductionmentioning
confidence: 99%
“…24) In addition to •OH, other reactive species, such as O 3, and energetic species, such as electrons and ions, contribute to the decomposition of various organic compounds. Several types of plasma reactors have been proposed, including pulsed corona discharge in water, 25) DC or pulsed corona discharge over water, [26][27][28] pulsed discharge over water, [29][30][31][32] DC or pulsed discharge in bubbles, [33][34][35][36][37] dielectric-barrier discharge (DBD) in a gas-liquid two-phase flow, 19,38) microwave plasma in water, 39) DBD in a mist flow, 40) DBD with a falling water film, 41,42) and pulsed plasma with droplets. 43,44) Because these plasma methods can operate without the addition of chemicals, they have significant advantages over AOPs that use chemicals for the treatment of wastewater at offshore plants and environmental water in remote areas.…”
Section: Introductionmentioning
confidence: 99%
“…1) However, these traditional AOPs do not have high efficiency for OH radical formation. 2) In order to improve decomposition efficiency by AOPs, the degradation of persistent organic pollutants using the OH radicals produced by discharge plasmas has been actively studied by many researchers [2][3][4][5][6][7] and has received a lot of attention as the next-generation technology for AOPs. Although there are many types of water treatment reactors based on the discharge plasma, most of the reactors utilize the pulsed corona discharge excited in water, in bubbles in water, in water droplets or on water surfaces using a pulsed power source.…”
Section: Introductionmentioning
confidence: 99%